Ansiedad por separación causada por divorcio de los padres y su impacto en un niño de 10 años de la Escuela de Educación Básica 10 de agosto - Chango Gorotiza, Gislley Shirley (2021)
This clinical case on separation anxiety caused by parental divorce and its impact on a 10-year-old boy from elementary school, August 10, in which a psychotherapeutic planning with a cognitive-behavioral approach was developed, in which It was possible to identify and elaborate a presumptive diagnosis such as 309.21 Separation anxiety disorder, which was corroborated by complying with the DSM-V criteria, being determined with the help of one psychometric evaluation such as the Spence anxiety scale. It was identified that the patient presented a significant symptomatology of anxiety, which was directly affecting his academic performance, the parents when observing said behavior made the decision to put aside their differences for a moment and negotiate regarding their responsibilities and roles as parents. For which an approach focused on psychoeducation and how to handle the divorce process was carried out without the patient being affected.